Consciousness Beyond Neural Fields: Expanding the Possibilities of What Has Not Yet Happened - Dresp-Langley, Birgitta (Frontiers in Psychology, 2022)
In the field theories in physics, any particular region of the presumed space-time continuum and all interactions between elementary objects therein can be objectively measured and/or accounted for mathematically. Since this does not apply to any of the field theories, or any other neural theory, of consciousness, their explanatory power is limited. As discussed in detail herein, the matter is complicated further by the facts than any scientifically operational definition of consciousness is inevitably partial, and that the phenomenon has no spatial dimensionality. Under the light of insights from research on meditation and expanded consciousness, healthy ageing, and eudaimonic well-being, it may be postulated that consciousness has evolved as mental energy generating forces beyond space and time (as measured in physics) to enable the human species to cope with unprecedented and/or unpredictable adversity. Such coping could, ultimately, include the conscious planning of our own extinction when survival on the planet is no longer an acceptable option.